2020
DOI: 10.21608/jppp.2020.103576
|View full text |Cite
|
Sign up to set email alerts
|

Bioefficacy of Bacterium, Pseudomonas fluorescens using Foliar Spray and Cultivated Soil Application against Tetranychus urticae on Cucumber Plants Comparing with an Acaricide

Abstract: The entomopthogenic bacterium , Pseudomonas fluorescens, was used alone as soil treatment and foliar application or mixed with entomopthogenic fungus , Beauveria bassiana for controlling the two spotted spider mite , Tetranychus urticae infesting Cucumber plants comparing with a standard synthetic acaricide ortus. P. fluorescens great effect as soil treatment and foliar spraying, recording reduction percentage of 75.21%. and no significant differences (df =6; P =<0.01) with the reduction caused by the acaricid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Few bacteria however have been investigated, due to the mites' piercing-sucking mouthparts, which make bacterial infection rare (Li et al 2018). Use of Pseudomonas species has been investigated (Aksoy et al 2008;Qessaoui et al 2017;Waked et al 2020), though reports are lacking on the effect of Pseudomonas secondary metabolites against T. urticae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few bacteria however have been investigated, due to the mites' piercing-sucking mouthparts, which make bacterial infection rare (Li et al 2018). Use of Pseudomonas species has been investigated (Aksoy et al 2008;Qessaoui et al 2017;Waked et al 2020), though reports are lacking on the effect of Pseudomonas secondary metabolites against T. urticae.…”
Section: Introductionmentioning
confidence: 99%
“…Qessaoui et al (2017) showed that the survival rate of adults of T. urticae was reduced by three uorescent Pseudomonas bacterial isolates Q110B, Q036B and Q172B. Field e cacy of P. uorescens on T. urticae adults has also been demonstrated Waked et al (2020). reported that soil and foliar application of P. uorescens showed great reduction of the population of T. urticae infesting cucumber plants.…”
mentioning
confidence: 99%